Reversible Capacity Enhancement of Zinc-Manganese Mixed Oxide through Nanoscale Electrochemical Wiring with Carbon Nanotubes - Yoon, Seung-Beom; Lee, Suk-Woo; Lee, Chang-Wook; Park, Sang-Loon; Kim, Hyun-Kyung; Nam, Kyung-Wan; Chung, Kyung-Yoon; Roh, Kwang Chul; Kim, Kwang-Bum (ELECTROCHEMICAL SOC INC, 2015)
Zinc-manganese mixed oxide (ZMO)/carbon nanotube (CNT) composites are synthesized based on an electronic wiring design for use in Li-ion batteries. The resulting composite consists of ZMO nanoparticles in intimate contact with CNT. The ZMO nanoparticles, which are in the electrical wiring with the CNTs, exhibit an additional conversion reaction involving MnO/Mn3O4, resulting in an enhanced reversible capacity up to 1050 mA h g(-1), which exceeds the theoretical reversible capacity of ZnMn2O4 (780 mA h g(-1)). During the synthesis of the ZMO/CNT composite, calcination in the presence of NH3 gas not only inhibits the oxidative decomposition of the CNTs but also reduces the oxidation state of Mn in the resulting composite. The elimination of superfluous oxygen (decrease in oxidation state of Mn in ZMO) leads to a decrease in irreversible capacities during the first cycle, directly related to energy efficiency. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: LITHIUM-ION BATTERIES; VOLTAMMETRIC CHARGE ANALYSIS; ANODE MATERIAL; ZNMN2O4 NANORODS; STORAGE MATERIAL; PERFORMANCE; LI; COMPOSITE; GRAPHENE; ELECTRODES